Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/cncr.28906
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer in Wilms tumor survivors: New insights into primary and secondary prevention

Abstract: The treatment of Wilms tumor (WT) is one of the great success stories in the field of oncology. Five-year overall survival (OS) estimates are 90% using modern treatment regimens, including surgery, chemotherapy, and radiotherapy (RT). 1 However, WT survivorship comes at a cost, as meticulously demonstrated by the Childhood Cancer Survivor Study (CCSS) and the National Wilms Tumor Late Effects Study (NWTS). [2][3][4] In the CCSS cohort, the cumulative incidence of chronic health conditions among survivors of WT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Malignant tumors are a well-documented late complication of therapy for Wilms tumor. 1 Lange et al reported that female survivors of Wilms tumor who were treated with radiotherapy to the thorax at a dose of 12 to 14 gray (Gy) had an elevated risk of developing early breast cancer, with nearly 15% having invasive disease by age 40 years. 2 Radiotherapy to the thorax is a risk factor for male breast cancer as well.…”
Section: Wilms Tumor and Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant tumors are a well-documented late complication of therapy for Wilms tumor. 1 Lange et al reported that female survivors of Wilms tumor who were treated with radiotherapy to the thorax at a dose of 12 to 14 gray (Gy) had an elevated risk of developing early breast cancer, with nearly 15% having invasive disease by age 40 years. 2 Radiotherapy to the thorax is a risk factor for male breast cancer as well.…”
Section: Wilms Tumor and Breast Cancermentioning
confidence: 99%
“…Males account for <1% of breast cancers diagnosed in the United States, and the disease is especially rare in younger men. 1 Using data from the 9th (1973-1991), 13th (1992-1999), and 18th (2000-2010) Surveillance, Epidemiology, and End Results registries, we calculated incidence rates of invasive plus in situ breast cancer for men and women aged <40 years of 0.0433 and 13.99 per 100,000 person-years, respectively. This yielded a male:female (M:F) ratio of 0.0031.…”
Section: Reply To Wilms Tumor and Breast Cancermentioning
confidence: 99%
“…We thank Drs. Lehrer and Rosenzweig for their insightful comments and opportunity to expand on our discussion regarding breast cancer in survivors of Wilms tumor . We acknowledge that the development of breast cancer in men was not specifically addressed in our comments.…”
mentioning
confidence: 99%